REFUSAL STRATEGIES TO INVITATION BY NATIVE AND NON NATIVE SPEAKERS OF ENGLISH - Agus Wijayanto (Universitas Muhammadiyah Surakarta, 2013)
ABSTRACTIn Javanese context, refusal tends to threat the feelings and self worth of addresseeswhile in British, refusal is not normally face threatening or at least it is notas face threatening as it is in the Javanese context. This paper compares sequencingof semantic formulae and adjuncts of refusal to invitations phrased by nativespeakers of British English and Javanese learners of English. The data of refusalare elicited through written discourse completion tasks (DCT) involving nine scenarios.Refusal strategies are classified based on a modified version of refusal taxonomyby Beebe, Takahashi, and Uliss-Weltz (1990). Overall the refusal strategiesemployed by the two groups are similar. Few differences in sequencing of semanticfomulae and adjuncts of refusal are due to politeness function.Keywords: refusal, sequential order, semantic formula, adjunct.